The Need for a New Paradigm in Scandinavian Health Economics - Gavin Mooney; Gustav Tinghög; Almina Kalkan (University of Oslo, 2012)
This paper argues that the discipline of health economics has lost its way due to its persistent focus on individualistic and consequential values. The paper suggests how this might be remedied in both theory and practice. It proposes a new paradigm for health economics, which focuses on communitarian values. This new paradigm is discussed in the context of the Scandinavian welfare model.